Purificación de aguas lluvias (2023)
The scarcity of water resources is one of the most worrying problems worldwide, since, as we all know, it is a necessary resource not only for human life, but also for the development of an ecosystem in general. There have been cases in which the lack of drinking water causes effects on the health of people and/or animals; This is because the current sanitary conditions for the treatment and use of water are ineffective and unsustainable. Some sectors of the world do not have access to water resources, not even to cover their basic needs, such as eating, removing biological waste or taking a bath. Thanks to the misuse of drinking water, diseases and infections that can cause death have been detected and/or found. For this reason, opportunities have been opened for research that aims to search for innovative projects that allow alternatives for access to drinking water and for domestic use for sectors that do not have access to them.